Silver-alkaline earth metal-containing MFI type zeolite and catalyst for hydrocarbon production

JP7632039B2Active Publication Date: 2025-02-19TOSOH CORP
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2021078304
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-05-06
Publication Date
2025-02-19
Estimated Expiration
2041-05-06

AI Technical Summary

Benefits of technology

【0043】 本発明は、新規な銀-アルカリ土類金属を含む特定のMFI型ゼオライトに関するものであり、特に脂肪族炭化水素から軽質炭化水素化合物及び芳香族化合物を同時製造する際に、特異的に高収率でバランスよく、かつ長い触媒寿命を得ることができる炭化水素化合物製造用触媒とすることも可能なものであり、工業的にも非常に有用なものである。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007632039000001
    Figure 0007632039000001
Patent Text Reader

Abstract

To provide a novel silver-alkaline earth metal-containing MFI-type zeolite that can simultaneously produce light hydrocarbon compounds and aromatic compounds from an aliphatic hydrocarbon at high yield, exhibits excellent performance in productivity, stability, and long life at that time, and can be applied as a catalyst for simultaneous production of the light hydrocarbon compounds and the aromatic compounds.SOLUTION: A silver-alkaline earth metal-containing MFI-type zeolite satisfies characteristics shown in the following (i) to (v). (i) An average particle diameter (PD) is PD≤100 nm. (ii) The alkaline earth metal-containing MFI type zeolite has a mesopore group having a mesopore distribution curve with a peak, a half value width (hw) of the peak of hw≤20 nm, a central value (μ) of the peak at 10 nm≤μ≤20 nm, and mesopore volume (pv) of the mesopore corresponding to the peak of 0.05 ml / g≤pv. (iii) There is no peak in a range of 0.1 to 3 degrees in powder X-ray diffraction measurement with a diffraction angle set to 2θ. (iv) A silver content is 0.05 to 3 wt.%. (v) A content of the alkaline earth metal is 0.05-5 wt.%.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a metal-containing MFI type zeolite having silver and an alkaline earth metal introduced therein, and a catalyst for producing hydrocarbons comprising the same. More specifically, the present invention relates to a catalyst for producing hydrocarbons, which is a catalyst for simultaneously producing light hydrocarbon compounds and aromatic compounds, and which exhibits excellent performance in terms of productivity, stability and long life when producing aromatic compounds from aliphatic hydrocarbons, by having a specific average particle size and specific amounts of silver and alkaline earth metal, and which enables the simultaneous production of light hydrocarbon compounds and aromatic compounds, which enables the production of light C2-C3 hydrocarbon compounds in a good balance at a high yield. [Background technology]

[0002] MFI zeolite is used as a highly selective catalyst that utilizes uniform pores derived from the zeolite structure. Examples of using MFI zeolite as a catalyst include disproportionation of toluene (see, for example, Patent Document 1) and isomerization of xylene (see, for example, Patent Document 2).

[0003] These reactions mainly utilize the characteristics of the micropores in MFI zeolite, which have an entrance diameter of approximately 0.5 nm and are thought to be effective reaction sites for molecules with molecular diameters close to the pore diameter.

[0004] Furthermore, research is being conducted on MFI zeolites having pores larger than micropores (less than 2 nm), that is, mesopores (pore diameter 2 to 50 nm) (see, for example, Non-Patent Document 1).

[0005] As a promising material for industrial use, a new MFI type zeolite with uniform mesopores of 10 nm or more and a method for producing the same have been proposed (see, for example, Patent Document 3). However, there have been only a few reports of specific results being obtained by using zeolites with mesopores as catalysts, particularly in reactions using relatively small molecules with 10 or less carbon atoms as raw materials.

[0006] Benzene, toluene, and xylene (hereinafter, collectively referred to as aromatic compounds) are often obtained by decomposing feedstock oil (e.g., naphtha, etc.) obtained by petroleum refining in a thermal cracking reactor, and separating and refining aromatic compounds from the obtained thermal cracking products by distillation or extraction. In the production of aromatic compounds by these production methods, aliphatic hydrocarbons (including paraffinic, olefinic, acetylene, and alicyclic) are included as thermal cracking products other than aromatic compounds. Therefore, since aliphatic hydrocarbons are simultaneously produced along with the production of aromatic compounds, the production amount of aromatic compounds is adjusted according to the production amount of aliphatic hydrocarbons, and the production amount is naturally limited. In addition, aromatic compounds can be produced by contacting an aliphatic hydrocarbon raw material with a catalyst mainly containing medium pore size zeolite at a temperature of about 400°C to about 800°C (for example, see Non-Patent Documents 2 to 5). Compared with the production method of aromatic compounds by thermal cracking, this production method has the advantage that it has low added value and can produce aromatic compounds from surplus hydrocarbon raw materials. Catalysts for use in the production of these aromatic compounds have also been developed. For example, as a catalyst for producing aromatic compounds using hydrocarbons containing paraffins, olefins, and naphthenes as raw materials, a zinc-supported medium pore size zeolite catalyst with reduced zinc scattering has been provided (see, for example, Patent Document 4). In addition, as a catalyst for producing aromatic compounds using paraffins, olefins, acetylene-based hydrocarbons, cyclic paraffins, and cyclic olefins as raw materials, a catalyst in which platinum and a halogen component are simultaneously supported on L-type zeolite has been provided (see, for example, Patent Document 5). Furthermore, a catalyst for aromatization reaction has been provided, which is characterized in that zinc and / or gallium are supported on a structure having a size of 0.1 to 100 mm, a crystalline porous aluminosilicate present on the surface layer of the structure, and an inorganic support present in the inner layer except for the surface layer of the structure (see, for example, Patent Document 6). In addition, catalysts for producing aromatic compounds using hydrocarbons as raw materials have been provided (see, for example, Patent Documents 7 and 8). In recent years, there have been developed aromatic compound production catalysts containing specific MFI type zeolites (see, for example, Patent Document 9), and silver-containing zeolites having high heat resistance and hydrothermal resistance (see, for example, Patent Document 10).), etc. have been proposed. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Patent No. 4014279 [Patent Document 2] Patent No. 2598127 [Patent Document 3] JP 2013-227203 A [Patent Document 4] Japanese Patent Application Publication No. 10-33987 [Patent Document 5] Patent No. 3264447 [Patent Document 6] Patent No. 5447468 [Patent Document 7] Patent No. 3966429 [Patent Document 8] Patent No. 5564769 [Patent Document 9] JP 2017-127857 A [Patent Document 10] JP 2018-154538 A [Non-patent literature]

[0008] [Non-Patent Document 1] Microporous and Mesoporous Materials, Vol. 137, p. 92 (2011) [Non-Patent Document 2] Industrial & Engineering Chemistry Research, Vol. 31, p. 995 (1992) [Non-Patent Document 3] Industrial & Engineering Chemistry Research, Vol. 26, p. 647 (1987) [Non-Patent Document 4] Applied Catalysis Vol. 78, p. 15 (1991) [Non-Patent Document 5] Microporous and Mesoporous Materials, Vol. 47, p. 253 (2001) Summary of the Invention [Problem to be solved by the invention]

[0009] However, in the methods for producing aromatic compounds using catalytic reactions provided by Patent Documents 4 to 8, there was a problem with the catalyst life (the time from when the catalyst is active after the start of the reaction until it becomes inactive) from the viewpoint of production costs. In addition, the proposals in Patent Documents 9 and 10 were effective from the viewpoint of producing aromatic compounds, but no consideration was given to the viewpoint of producing light hydrocarbon compounds.

[0010] The present invention provides a novel catalyst that enables the simultaneous, selective, and balanced production of light hydrocarbon compounds (hydrocarbon compounds having 2 to 3 carbon atoms) and aromatic compounds from aliphatic hydrocarbons having relatively small molecules (particularly those having 10 or less carbon atoms, preferably 4 to 6 carbon atoms) in high yields in a stable manner over a long period of time, and a metal-containing MFI type zeolite that can be used therein. [Means for solving the problem]

[0011] Means for Solving the Problems The present inventors have conducted intensive research to solve the above problems, and as a result have found that a specific MFI type zeolite into which silver and an alkaline earth metal have been introduced can serve as a catalyst that enables the simultaneous production of light hydrocarbon compounds and aromatic compounds from aliphatic hydrocarbons selectively, stably over a long period of time, and in a balanced and high yield, thereby completing the present invention.

[0012] That is, the present invention relates to a silver-alkaline earth metal-containing MFI type zeolite characterized by satisfying the following characteristics (i) to (v), and a catalyst for simultaneously producing light hydrocarbon compounds and aromatic compounds comprising the same. (i) The average particle diameter (PD) is PD≦100 nm. (ii) The mesopore distribution curve has a peak, the half width (hw) of the peak is hw≦20 nm, the center value (μ) of the peak is 10 nm≦μ≦20 nm, and the mesopore volume (pv) of the mesopores corresponding to the peak is 0.05 ml / g≦pv. (iii) In powder X-ray diffraction measurement at a diffraction angle of 2θ, there is no peak in the range of 0.1 to 3 degrees. (iv) The silver content is 0.05 to 3 wt%. (v) The alkaline earth metal content is 0.05 to 5 wt%.

[0013] The present invention will be described in detail below.

[0014] The novel silver-alkaline earth metal-containing MFI type zeolite of the present invention satisfies the characteristics (i) to (v) shown above, and the MFI type zeolite refers to an aluminosilicate compound belonging to the structure code MFI defined by the International Zeolite Association.

[0015] The novel silver-alkaline earth metal-containing MFI zeolite of the present invention has (i) PD≦100 nm, and since it is a zeolite with particularly excellent thermal stability, it is desirable that 5 nm≦PD≦100 nm. Here, if the PD exceeds 100 nm, the reaction efficiency will be poor when used as a catalyst for the conversion reaction of hydrocarbons.

[0016] The method for measuring PD in the present invention is not limited, and any method can be used, such as a method of selecting 100 or more particles from a photograph taken with a scanning electron microscope (SEM) or a transmission electron microscope (TEM) and determining their average diameter, or a method of calculating the PD from the external surface area of ​​zeolite using the following formula (1). PD = 6 / S × (1 / (2.29 × 10 6 ) + 0.18 × 10 -6 ) (1) (Here, S is the external surface area (m 2 / g) In addition, the external surface area (S(m 2 The surface area of ​​the zeolite is calculated by the slope of the regression line obtained by linear approximation of the measurement points in the range of 0.6 to 1 nm for t, where t is the thickness of the adsorption amount.

[0017] Among these, the method using SEM or TEM is preferable since it allows simple measurement.

[0018] The novel silver-alkaline earth metal-containing MFI type zeolite of the present invention (ii) has a mesopore distribution curve having a peak, the half width (hw) of the peak is hw≦20 nm, the center value (μ) of the peak is 10 nm≦μ≦20 nm, and the mesopore volume (pv) of the mesopores corresponding to the peak is 0.05 ml / g≦pv. The mesopores referred to in the present invention are mesopores defined by IUPAC and indicate pores with a pore diameter in the range of 2 to 50 nm. The mesopores can be measured by a general nitrogen adsorption method at liquid nitrogen temperature. In addition, the value of the pore volume of the mesopores can be obtained by analyzing the measurement results obtained by the nitrogen adsorption method. For example, the following method can be used for the analysis.

[0019] Specifically, the desorption process can be analyzed by the Barret-Joyner-Halenda method (Journal of the American Chemical Society, 1951, pp. 373-380). For example, by integrating the amount of nitrogen gas desorbed in the range corresponding to a pore diameter of 2 nm or more and 50 nm or less, the total pore volume of pores belonging to mesopores can be obtained.

[0020] In addition, first, a cumulative curve is obtained with the nitrogen desorption amount per unit mass V / m (mL / g) on ​​the vertical axis and the mesopore diameter D (nm) on the horizontal axis, and then the vertical axis is changed to the differential value (d(V / m) / d(D)) of the nitrogen gas desorption amount from the mesopores with respect to the mesopore diameter value, whereby the peak of the increase in the nitrogen desorption amount per unit mass at the mesopore diameter can be obtained.

[0021] The novel silver-alkaline earth metal-containing MFI zeolite of the present invention comprises an MFI zeolite having a group of mesopores with a nearly uniform pore diameter, and in the present invention, the group of mesopores with a nearly uniform pore diameter may be referred to as uniform mesopores. Specifically, the uniform mesopores refer to mesopores having a pore diameter within a range (μ±2σ) of twice the standard deviation (2σ) from the central value (μ) of the Gaussian function, which is obtained by approximating the maximum peak among the peaks related to mesopores in the pore distribution curve with a Gaussian function. The pore volume of the uniform mesopores can be calculated by integrating the amount of nitrogen gas desorbed within the range of μ±2σ.

[0022] The silver-alkaline earth metal-containing MFI zeolite of the present invention comprises, among MFI zeolites having a substantially uniform group of mesopores, (ii) an MFI zeolite having a more uniform group of mesopores, in which the mesopore distribution curve has a peak, the half width (hw) of the peak is hw≦20 nm, the center value (μ) of the peak is 10 nm≦μ≦20 nm, and the mesopore volume (pv) of the mesopores corresponding to the peak is pv≧0.05 ml / g.

[0023] The silver-alkaline earth metal-containing MFI zeolite of the present invention has an excellent reaction selectivity by containing an MFI zeolite having a peak in the pore distribution curve of the mesopores, the peak being an MFI zeolite having a group of almost uniform mesopores with small variation in the pore diameter size, that is, an MFI zeolite having hw≦20 nm or less, and the effect is more remarkable and preferable when hw≦15 nm, particularly hw≦10 nm. The lower limit of hw is not particularly limited, but it is preferable that it is 1 nm or more because it will have a better reaction selectivity. Note that if hw>20 nm, the reaction selectivity will be poor when used as a catalyst for producing hydrocarbon compounds. In addition, by containing an MFI zeolite having a center value (μ) of 10 nm≦μ≦20 nm when the peak is approximated by a Gaussian function, it becomes possible to selectively react even molecules of larger sizes, and it becomes an excellent catalyst for producing hydrocarbon compounds. Furthermore, by satisfying pv≧0.05 ml / g, the catalyst used will have a long life for producing hydrocarbon compounds, and 0.05 ml / g≦pv≦0.70 ml / g is preferable, 0.10 ml / g≦pv≦0.70 ml / g is particularly preferable, and 0.20 ml / g≦pv≦0.50 ml / g is even more preferable. Here, if pv<0.05 ml / g, the pores will be easily clogged due to the accumulation of coke and other by-products produced during the reaction, resulting in a poor catalyst life when used.

[0024] Furthermore, since the silver-alkaline earth metal-containing MFI type zeolite of the present invention is particularly suitable as a catalyst for producing hydrocarbon compounds that enables selective reactions, it is preferable that the ratio (pvr) of pv shown in (ii) above to the total pore volume be 30%≦pvr≦100%, and more preferably 40%≦pvr≦100%.

[0025] The silver-alkaline earth metal-containing MFI zeolite of the present invention (iii) has no peak in the range of 0.1 to 3 degrees in powder X-ray diffraction measurement with a diffraction angle of 2θ. This indicates that there is no regularity in the arrangement of mesopores and that there are no walls separating the mesopores. When used as a catalyst, the material transfer between the mesopores becomes easy, and the zeolite serves as a catalyst for producing hydrocarbon compounds with excellent reaction efficiency.

[0026] The silver-alkaline earth metal-containing zeolite of the present invention has a silver content of 0.05 to 3 wt%, and by having a silver content within a specific range, the zeolite exhibits particularly excellent catalytic performance when used as a catalyst for producing hydrocarbon compounds. Here, if the silver content is less than 0.05 wt%, the acid site protection effect of silver cannot be obtained, and the catalyst performance in terms of production efficiency and selectivity when used as a catalyst for producing hydrocarbon compounds is inferior. On the other hand, if the silver content exceeds 3 wt%, the aggregation of silver progresses, and side reactions and coking are likely to occur on the surfaces of the silver aggregated particles, resulting in a deterioration in catalytic performance.

[0027] The silver-alkaline earth metal-containing zeolite of the present invention (v) has an alkaline earth metal content of 0.05-5 wt%, and contains an alkaline earth metal within a specific range, making it useful as a catalyst for simultaneous production of light hydrocarbon compounds and aromatic compounds, which enables simultaneous, selective and long-term stable production of light hydrocarbon compounds and aromatic compounds from aliphatic hydrocarbons. Examples of alkaline earth metals include calcium, strontium, barium, and radium, and in particular, one or more selected from the group consisting of calcium, strontium, and barium are preferable because they exhibit excellent properties as a catalyst for producing hydrocarbon compounds. Here, if the alkaline earth metal content is less than 0.05 wt%, the selectivity for light hydrocarbon compounds will be poor. Also, if it exceeds 5 wt%, the stability as a catalyst for simultaneous production will be poor.

[0028] The silver-alkaline earth metal-containing MFI type zeolite of the present invention has a SiO 2 / Al2 O 3 The molar ratio is not particularly limited, and among them, SiO is particularly preferred because it provides a catalyst for producing hydrocarbon compounds that is excellent in heat resistance, reaction selectivity, and productivity. 2 / Al 2 O 3 It is preferable that the molar ratio is 20 or more and 200 or less.

[0029] The silver-alkaline earth metal-containing MFI type zeolite of the present invention is preferably one that does not contain a structure-directing agent such as tetrapropylammonium salt within its pores, since it serves as a catalyst for producing hydrocarbon compounds with excellent reaction selectivity and productivity.

[0030] As a method for producing MFI zeolite, which is a raw material that satisfies the above characteristics (i) to (iii), the following method can be mentioned, for example.

[0031] Amorphous aluminosilicate gel is added to an aqueous solution of tetrapropylammonium (hereinafter sometimes referred to as "TPA") hydroxide and sodium hydroxide to form a suspension, and MFI type zeolite is added to the resulting suspension as seed crystals to form a raw material composition. The resulting raw material composition is crystallized and calcined to obtain MFI type zeolite.

[0032] The silver-alkaline earth metal-containing MFI zeolite of the present invention further preferably has (vi) an outer surface acid amount of 0.01 mmol / g or less, and particularly preferably 0.0001 to 0.01 mmol / g. Here, the outer surface acid site of a zeolite, as the term implies, indicates an acid site present on the outer surface of the zeolite. Usually, a zeolite has acid sites on its outer surface and in (micro)pores, and not having acid sites on the outer surface means that the zeolite has acid sites only in (micro)pores. And, since the zeolite has excellent heat resistance, hot water resistance, and durability, it is preferable that the silver-alkaline earth metal-containing MFI zeolite has an unmodified surface that is not coated with silicate, dialkylamine reagent, or the like.

[0033] The acid sites on the external surface of zeolites can be confirmed by any method that allows such confirmation. For example, they can be confirmed by adsorption of 2,4-dimethylquinoline, which has adsorptivity for acid sites (see Characterization of acid sites on the external surface of zeolites, Reaction Kinetics and Catalysis Letters, vol. 67, p. 281 (1999)).

[0034] The silver-alkaline earth metal-containing MFI type zeolite of the present invention preferably has an acid amount of (vii) 0.05 to 0.85 mmol / g, and particularly preferably 0.05 to 0.55 mmol / g. The acid amount can be measured by a method generally known as a method for measuring acid amount, for example, a method based on the ammonia-TPD method (see Measurement of solid acidity by ammonia temperature-programmed desorption method, Catalyst, vol. 42, p. 218 (2000)).

[0035] As a method for producing MFI zeolite satisfying any one of (vi) to (vii), for example, it is possible to produce it by dealuminating aluminum in the framework of MFI zeolite, which is a raw material satisfying the above characteristics (i) to (iii), with steam or the like. The temperature of the steam treatment is, for example, preferably 400 to 900°C, particularly preferably 450 to 800°C, and more preferably 500 to 700°C. The partial pressure of the steam is preferably 0.001 to 5 MPa, particularly preferably 0.01 to 0.5 MPa, and more preferably 0.05 to 0.2 MPa. The concentration of the steam is preferably, for example, 0.01 to 100 vol% water steam / dilution gas. The dilution gas may be an inert gas such as nitrogen, air, oxygen, carbon monoxide, carbon dioxide, or a mixture thereof. The steam treatment time can be selected arbitrarily.

[0036] Furthermore, since the silver-alkaline earth metal-containing MFI type zeolite of the present invention serves as a catalyst for the simultaneous production of light hydrocarbon compounds and aromatic compounds, which is particularly excellent in balance when these compounds are produced, it is preferable that the content ratio of silver and alkaline earth metal (viii) silver / alkaline earth metal (weight ratio) is in the range of 100 / 100 to 500 / 100.

[0037] The silver-alkaline earth metal-containing MFI zeolite of the present invention can be produced, for example, by incorporating silver and an alkaline earth metal into MFI zeolite by a method such as impregnation, ion exchange, or physical mixing.

[0038] The form in which the silver-alkaline earth metal-containing MFI type zeolite of the present invention is used as a catalyst for producing hydrocarbon compounds is not limited, and it is possible to use the silver-alkaline earth metal-containing MFI type zeolite powder as it is as a catalyst, to compress and mold it into a specific shape, or to mix it with a binder or the like and mold it into a specific shape, and so forth.

[0039] By using the silver-alkaline earth metal-containing MFI type zeolite of the present invention as a catalyst for producing hydrocarbon compounds, the catalyst becomes excellent in efficiency such as reaction selectivity and productivity, and by contacting it with, for example, an aliphatic hydrocarbon, particularly an aliphatic hydrocarbon having 10 or less carbon atoms, further an aliphatic hydrocarbon having 4 to 6 carbon atoms, it becomes possible to efficiently and balancedly produce light hydrocarbon compounds and aromatic compounds simultaneously. In this case, the aliphatic hydrocarbons include, for example, paraffinic, olefinic, acetylene, and alicyclic hydrocarbons, and specific examples thereof include paraffinic, such as butane, isobutane, pentane, and hexane; olefinic, such as butene, isobutene, pentene, and hexene; alicyclic, such as cyclohexane, and mixtures thereof.

[0040] In the reaction according to the embodiment, the reaction temperature is not particularly limited as long as it is possible to produce hydrocarbon compounds such as light hydrocarbon compounds and aromatic compounds. In particular, the reaction temperature is preferably in the range of 400 to 800°C, since it suppresses the production of by-products such as paraffins, olefins, or alkanes and provides an efficient reaction between light hydrocarbon compounds and aromatic compounds without requiring an excessively high-temperature reaction apparatus. There is also no limitation on the reaction pressure, and operation is possible within a pressure range of, for example, about 0.05 MPa to 5 MPa. The supply of aliphatic hydrocarbons, which are the reaction raw materials, to the catalyst for simultaneous production of light hydrocarbon compounds and aromatic compounds is not particularly limited as the ratio of the volume of the raw material gas to the volume of the catalyst, and may be, for example, 1 h. -1 ~50000h -1 When the aliphatic hydrocarbon is supplied as the raw material gas, it may be used as a single gas, a mixed gas, or a gas diluted with a single or mixed gas selected from an inert gas such as nitrogen, hydrogen, carbon monoxide, and carbon dioxide.

[0041] The reaction type is not limited, and for example, not only fixed bed, transport bed, fluidized bed, moving bed, and multi-tubular reactor, but also continuous flow type, intermittent flow type, and swing type reactors can be used.

[0042] The light hydrocarbon compounds produced include C2-C3 hydrocarbon compounds such as ethane, ethylene, propane, and propylene, with ethylene being particularly preferred. The aromatic compounds are not particularly limited as long as they fall within the category of aromatic compounds, and include, for example, benzene, toluene, xylene, trimethylbenzene, ethylbenzene, propylbenzene, butylbenzene, naphthalene, and methylnaphthalene, with benzene, toluene, and xylene being particularly preferred. Since this is a method for producing hydrocarbon compounds with a particularly excellent balance between the production of light hydrocarbon compounds and aromatic compounds, it is preferable to produce C2-C3 hydrocarbon compounds / aromatic compounds (weight ratio)=80 / 100-180 / 100. Effect of the Invention

[0043] The present invention relates to a specific MFI type zeolite containing a novel silver-alkaline earth metal, which can be used as a catalyst for producing hydrocarbon compounds, which can provide a specifically high yield, a good balance, and a long catalyst life, particularly when simultaneously producing light hydrocarbon compounds and aromatic compounds from aliphatic hydrocarbons, and is therefore extremely useful industrially. EXAMPLES

[0044] The present invention will be specifically described below with reference to examples.

[0045] The performance of the MFI zeolite used in the examples as a catalyst for the simultaneous production of light hydrocarbon compounds and aromatic compounds was measured and defined by the following methods.

[0046] ~Measurement of pore distribution, pore diameter, and external surface area~ The pore distribution and pore diameter of the MFI zeolite were measured by nitrogen adsorption measurement.

[0047] The nitrogen adsorption was measured using a nitrogen adsorption apparatus (product name: OMNISORP360CX, manufactured by Beckman Coulter) at 30 torr / step for both adsorption and desorption. The external surface area was calculated by linear approximation in the range of the adsorption layer thickness (t=0.6-1.0 nm) using the t-plot method.

[0048] The desorption process of the nitrogen adsorption measurement was analyzed by the Barret-Joyner-Halenda method (Journal of the American Chemical Society, 1951, pp. 373-380), and a mesopore distribution curve was obtained in which the horizontal axis is the pore diameter constant and the vertical axis is the differential value of the desorption amount of nitrogen gas. The total pore volume of mesopores was calculated by integrating the amount of desorption of nitrogen gas in the range of 2 nm to 50 nm.

[0049] The maximum peak of the differential value (d(V / m) / d(D)) of the amount of nitrogen gas desorbed from the mesopores with respect to the mesopore diameter value was analyzed using the intensity approximation of a Gaussian function, and mesopores with diameters within a range of twice the standard deviation (2σ) (=μ±2σ) from the center value (μ) of the Gaussian function were defined as uniform mesopores. The pore volume of uniform mesopores was calculated by integrating the amount of nitrogen gas desorbed within a range of ±2σ based on the center value (μ).

[0050] ~Measurement of average particle size~ The average particle size was calculated from the external surface area using the above formula (1). In formula (1), S is the external surface area (m 2 / g), and PD is the average particle diameter (m). 2 / g) was calculated from the t-plot method using the nitrogen adsorption method at liquid nitrogen temperature.

[0051] ~Measurement of silver and alkaline earth metal introduction amount~ The amount of silver and alkaline earth metal incorporated in the zeolite was determined by dissolving the MFI type zeolite in a mixed aqueous solution of hydrofluoric acid and nitric acid, and measuring the resultant solution by inductively coupled plasma atomic emission spectrometry (ICP-AES) using a general ICP apparatus (product name OPTIMA3300DV, manufactured by PerkinElmer).

[0052] ~Powder X-ray diffraction measurement~ An X-ray diffraction measurement device (Spectris, product name: X'pert PRO MPD) was used, and measurements were taken in air using CuKα1 at a tube voltage of 45 kV and a tube current of 40 mA. The range of 0.04 to 5 degrees was analyzed at 0.08 degrees / step and 200 seconds / step. In addition, the background corrected for the absorption rate of the direct beam was removed. The presence or absence of peaks was confirmed by visual inspection.

[0053] ~Measurement of the amount of outer surface acid~ The amount of external surface acid was measured by 2,4-dimethylquinoline adsorption infrared absorption spectroscopy. The measurement was performed by the transmission method using an FT-IR measurement device ((trade name) FT / IR-6700, manufactured by JASCO Corporation). The spectrum was obtained by 256 integration times using an MCT detector. The sample was molded into a disk with a diameter of 13 mm, and then placed in a disk holder in a quartz vacuum degassing cell, so that it was placed vertically on the infrared light path. As a pretreatment of the sample, the temperature was raised to 400°C at 10°C / min under vacuum evacuation and held for 2 hours. After cooling to 150°C, the infrared absorption spectrum before 2,4-dimethylquinoline adsorption was measured. 2,4-dimethylquinoline gas was introduced and adsorbed for 30 minutes, and after evacuation at 150°C for 1 hour, the infrared absorption spectrum after 2,4-dimethylquinoline adsorption was measured. The difference between the infrared absorption spectrum after 2,4-dimethylquinoline adsorption and the spectrum before adsorption was taken, and the change in infrared absorption due to adsorption was measured. In this difference spectrum, 3600 cm -1 The peak in this vicinity is the absorption spectrum peak of 2,4-dimethylquinoline adsorbed to the outer surface acid sites (Brønsted acid sites). After determining this integrated intensity, the amount of outer surface acid was calculated using the Lambert-Beerr law according to the following formula (2). Acid amount (μmol / mg)=A S / (W ε) (2) (where A is the peak area intensity of the peak of interest (cm -1 ), S: sample cross-sectional area (cm 2 ), W is the sample weight (mg), ε is the integrated extinction coefficient, 3.7 cm μmol -1 , respectively.) ~Acidity measurement~ The amount of acid was measured by pyridine adsorption infrared absorption spectroscopy. The same apparatus and method were used as in the above 2,4-dimethylquinoline adsorption infrared absorption spectroscopy, except that pyridine gas was introduced and allowed to adsorb for 10 minutes.

[0054] However, the difference spectrum at 1545 cm -1 The peak in the vicinity was used as the peak of the absorption spectrum of pyridine adsorbed on the Brønsted acid site, and the integrated extinction coefficient was set to 1.67 cm μmol -1The amount of acid was calculated using the above formula (2).

[0055] - Hydrocarbon compound manufacturing apparatus and manufacturing method thereof - The MFI zeolite obtained in the examples and the catalyst for simultaneous production of light hydrocarbon compounds and aromatic compounds containing the same were used to produce light hydrocarbon compounds and aromatic compounds by the following methods, and the results were evaluated.

[0056] A fixed-bed gas-phase flow reactor using stainless steel reaction tubes (inner diameter 16 mm, length 900 mm) was used. A catalyst for producing hydrocarbon compounds was packed in the middle of each stainless steel reaction tube, and after performing a heating pretreatment under a dry air flow, the raw material gas was fed. The reactor equipment conditions and operating conditions are not limited to those described in this example, and can be selected as appropriate. A ceramic tubular furnace was used for heating, and the temperature of the catalyst layer was controlled. The reaction outlet gas and reaction liquid were collected, and the gas components and liquid components were analyzed individually using a gas chromatograph. The gas components were analyzed using a gas chromatograph (Shimadzu Corporation, (trade name) GC-1700) equipped with a TCD detector. The packing material used was Waters' PorapakQ (trade name) or GL Science's MS-5A (trade name). The liquid components were analyzed using a gas chromatograph (Shimadzu Corporation, (trade name) GC-2015) equipped with an FID detector. The separation column used was a capillary column (product name: TC-1, manufactured by GL Sciences).

[0057] The reaction conditions were set as follows:

[0058] (Manufacturing conditions) Catalyst temperature: 585℃. Gas flow: Mixture of 1-butene 125 ml / min, 2-butene 75 ml / min, isobutene 225 ml / min, normal butane 50 ml / min, and isobutane 25 ml / min. Catalyst weight: 70.0g. Reaction pressure: 0.1MPa.

[0059] Preparation Example 1 The MFI type zeolite was produced with reference to JP 2013-227203 A.

[0060] Amorphous aluminosilicate gel was added to an aqueous solution of tetrapropylammonium (hereinafter sometimes abbreviated as TPA) hydroxide and sodium hydroxide and suspended. MFI type zeolite was added as seed crystals to the resulting suspension to prepare a raw material composition. The amount of seed crystals added was determined based on the amount of Al in the raw material composition. 2 O 3 and SiO 2 The concentration was 0.7% by weight based on the weight of the mixture. The by-product ethanol was removed by evaporation.

[0061] The composition of the raw material composition is as follows: SiO 2 / Al 2 O 3 molar ratio = 47, TPA / Si molar ratio = 0.05, Na / Si molar ratio = 0.17, OH / Si molar ratio = 0.21, H 2 O / Si molar ratio=10 The obtained raw material composition was sealed in a stainless steel autoclave and crystallized for 4 days while stirring at 115°C to obtain a slurry mixture. After the crystallization, the slurry mixture was subjected to solid-liquid separation using a centrifugal settler, and the solid particles were washed with a sufficient amount of pure water and dried at 110°C to obtain a dry powder.

[0062] The obtained dry powder was dispersed in 1 mol / L hydrochloric acid at room temperature, filtered, the solid particles were washed with a sufficient amount of pure water, filtered again, and dried overnight at 100°C. It was calcined in air at 550°C for 1 hour, and then treated with 30% water vapor at 600°C for 2 hours. The obtained powder was dispersed in 1 mol / L hydrochloric acid at room temperature, filtered, the solid particles were washed with a sufficient amount of pure water, filtered again, and zeolite was obtained.

[0063] The obtained MFI type zeolite had an average particle size of 39 nm, an outer surface acid amount of 0.003 mmol / g, and an acid amount of 0.24 mmol / g.

[0064] Preparation Example 2 100 parts by weight of the MFI zeolite obtained in Preparation Example 1 were mixed with 43 parts by weight of silica (manufactured by Nissan Chemical Industries, Ltd., (product name) Snowtex N-30G), 4 parts by weight of cellulose, and 20 parts by weight of pure water, and then kneaded. The kneaded product was formed into a cylindrical molded body having a diameter of 1.5 mm and a length of 1.0 to 7.0 mm (average length 3.5 mm). This was dried overnight at 100°C, and then calcined in air at 550°C for 1 hour. The obtained MFI zeolite molded body had an average particle size of 35 nm, an outer surface acid amount of 0.003 mmol / g, and an acid amount of 0.20 mmol / g.

[0065] Preparation Example 3 Silver was supported on the MFI zeolite molded body obtained in Preparation Example 2 by ion exchange. 300 parts by weight of pure water and 8 parts by weight of silver nitrate were used for 100 parts by weight of the MFI zeolite molded body obtained in Preparation Example 2. Silver nitrate was dissolved in pure water to prepare an aqueous silver nitrate solution, the zeolite molded body was added, and the aqueous solution was circulated in a dark place for 6 hours using a circulation pump. After washing with pure water, the product was dried overnight at 110°C, heated to 550°C and calcined for 6 hours to prepare a silver-containing zeolite molded body. The obtained silver-containing zeolite shaped body had a 10-membered ring framework structure, an average particle size of 32 nm, an outer surface acid amount of 0.003 mmol / g, an acid amount of 0.19 mmol / g, and a silver content of 1.4 wt %.

[0066] Example 1 The MFI zeolite compact obtained in Preparation Example 2 was loaded with calcium by impregnation. 3.1 g of calcium acetate was dissolved in 2.0 L of pure water, and 1050 g of MFI zeolite compact was added and immersed at room temperature for 30 minutes. Then, the compact was immersed in 2.0 L of pure water for 5 minutes. This immersion in the calcium acetate aqueous solution and pure water was repeated three times. Then, the zeolite was transferred to a magnetic dish, heated to 110°C, and dried overnight. The compact was then heated to 550°C and fired for 6 hours to obtain a calcium-containing zeolite compact.

[0067] The calcium-containing zeolite compact thus obtained was subjected to silver loading by impregnation. 3.1 g of silver nitrate was dissolved in 350 ml of pure water, and 108 g of the calcium-containing zeolite was added to the aqueous solution and immersed at room temperature for 2 hours. After washing with pure water, the zeolite was dried overnight at 110°C and calcined at 550°C for 6 hours to obtain a silver-calcium-containing MFI type zeolite compact.

[0068] The obtained silver-calcium-containing MFI type zeolite had a 10-membered ring framework structure, and the mesopore distribution curve in the pore distribution curve had a peak, and the half-width of the uniform mesopore peak was 10 nm, μ = 18 nm. The pore volume of the uniform mesopores was 0.36 ml / g, and the ratio of the pore volume of the uniform mesopores to the total pore volume of the mesopores was 83%. In the powder X-ray diffraction, there was no peak in the range of 0.1 to 3 degrees, the average particle diameter was 28 nm, the amount of outer surface acid was 0.003 mmol / g, the amount of acid was 0.16 mmol / g, the silver content was 1.1 wt%, the calcium content was 0.3 wt%, and the silver / calcium (weight ratio) was 380 / 100.

[0069] The silver-calcium-containing MFI type zeolite shaped body was used as a catalyst for producing hydrocarbon compounds, and the reaction was carried out for 48 hours as described above. The average yield of each product during the reaction is shown in Table 1. The average yield of light hydrocarbon compounds (the total of ethane, ethylene, propane, and propylene) was 38.7% by weight, the average yield of aromatic compounds (the total of benzene, toluene, and xylene) was 38.6% by weight, and the total yield of light hydrocarbon compounds and aromatic compounds was 77.3% by weight. As a catalyst for the simultaneous production of light hydrocarbon compounds and aromatic compounds, it exhibited excellent balance and total yield.

[0070] Example 2 The silver-containing zeolite compact obtained in Preparation Example 3 was loaded with calcium by impregnation. 0.3 g of calcium hydroxide was dissolved in 200 ml of pure water, and 105 g of the silver-containing zeolite compact was added and immersed at room temperature for 30 minutes. Then, the compact was immersed in 200 ml of pure water for 15 minutes. This immersion in the calcium hydroxide aqueous solution and the pure water was repeated twice. Then, the zeolite was transferred to a magnetic dish, heated to 110°C, and dried overnight. The temperature was then raised to 550°C and calcined for 6 hours to obtain a silver-calcium-containing MFI type zeolite compact.

[0071] The obtained silver-calcium-containing MFI type zeolite had a 10-membered ring framework structure, and the mesopore distribution curve in the pore distribution curve had a peak, and the half-width of the uniform mesopore peak was 10 nm, μ = 17 nm. The pore volume of the uniform mesopores was 0.36 ml / g, and the ratio of the pore volume of the uniform mesopores to the total pore volume of the mesopores was 82%. In the powder X-ray diffraction, there was no peak in the range of 0.1 to 3 degrees, the average particle size was 30 nm, the amount of outer surface acid was 0.003 mmol / g, the amount of acid was 0.18 mmol / g, the silver content was 1.4 wt%, the calcium content was 0.3 wt%, and the silver / calcium (weight ratio) was 460 / 100.

[0072] The silver and calcium-containing zeolite molded body was used as a catalyst for producing hydrocarbon compounds, and the reaction was carried out for 48 hours as described above. The average yield of each product during the reaction is shown in Table 1. The average yield of light hydrocarbon compounds (the total of ethane, ethylene, propane, and propylene) was 35.5% by weight, the average yield of aromatic compounds (the total of benzene, toluene, and xylene) was 42.4% by weight, and the total yield of light hydrocarbon compounds and aromatic compounds was 77.9% by weight. As a catalyst for the simultaneous production of light hydrocarbon compounds and aromatic compounds, it demonstrated an excellent balance and total yield.

[0073] Example 3 The silver-containing zeolite molded body obtained in Preparation Example 3 was loaded with calcium by impregnation. 0.3 g of calcium hydroxide was dissolved in 200 ml of pure water, and 105 g of the silver-containing zeolite molded body was added and immersed at room temperature for 30 minutes. Then, the molded body was immersed in 200 ml of pure water for 15 minutes. This immersion in the calcium hydroxide aqueous solution and the pure water was repeated six times. Then, the zeolite was transferred to a magnetic dish, heated to 110°C, and dried overnight. The molded body was then heated to 550°C and fired for six hours to obtain a silver-calcium-containing MFI type zeolite molded body.

[0074] The obtained silver-calcium-containing MFI type zeolite had a 10-membered ring framework structure, and the mesopore distribution curve in the pore distribution curve had a peak, and the half-width of the uniform mesopore peak was 10 nm, μ = 18 nm. The pore volume of the uniform mesopores was 0.35 ml / g, and the ratio of the pore volume of the uniform mesopores to the total pore volume of the mesopores was 81%. In the powder X-ray diffraction, there was no peak in the range of 0.1 to 3 degrees, the average particle size was 27 nm, the amount of outer surface acid was 0.002 mmol / g, the amount of acid was 0.15 mmol / g, the silver content was 1.4 wt%, the calcium content was 0.8 wt%, and the silver / calcium (weight ratio) was 173 / 100.

[0075] The silver-calcium-containing zeolite was used as a catalyst for producing hydrocarbon compounds, and the reaction was carried out for 48 hours as described above. The average yield of each product during the reaction is shown in Table 1. The average yield of light hydrocarbon compounds (the total of ethane, ethylene, propane, and propylene) was 46.9% by weight, the average yield of aromatic compounds (the total of benzene, toluene, and xylene) was 30.3% by weight, and the total yield of light hydrocarbon compounds and aromatic compounds was 77.2% by weight. As a catalyst for the simultaneous production of light hydrocarbon compounds and aromatic compounds, it exhibited excellent balance and total yield.

[0076] Comparative Example 1 The silver-containing zeolite shaped body obtained in Preparation Example 3 was used as a catalyst for producing hydrocarbon compounds, and the reaction was carried out for 48 hours as described above. The average yields of each product during the reaction are shown in Table 1. The average yield of light hydrocarbon compounds (the total of ethane, ethylene, propane, and propylene) was 18.0% by weight, the average yield of aromatic compounds (the total of benzene, toluene, and xylene) was 54.6% by weight, and the total yield of light hydrocarbon compounds and aromatic compounds was 72.6% by weight.

[0077] Priority was given to the production of aromatic compounds, and the production balance and productivity between light hydrocarbon compounds and aromatic compounds was poor.

[0078] Comparative Example 2 The MFI zeolite compact obtained in Preparation Example 2 was loaded with calcium by ion exchange. 2105 g of the MFI zeolite compact was filled up to a length of 40 cm in a PVC pipe having an inner diameter of 10.0 cm, and 6.2 g of calcium hydroxide was dissolved in 6700 ml of pure water to prepare a 12 mmol / L calcium hydroxide aqueous solution. A circulation pump and a PVC pipe were connected using a chemical-resistant polyolefin hose, and the calcium hydroxide aqueous solution was circulated at 26 cm / min for 60 minutes. After repeating this operation twice, all of the calcium hydroxide aqueous solution was extracted, and then 6700 ml of pure water was circulated at the same flow linear velocity for 15 minutes. After repeating this pure water circulation twice, the zeolite was collected on a magnetic dish, heated to 110°C, and dried overnight to obtain a calcium-containing MFI zeolite.

[0079] The calcium content of the obtained calcium-containing MFI type zeolite was 0.3 wt%, it had a 10-membered ring framework structure, the powder X-ray diffraction showed no peak in the range of 0.1 to 3 degrees, the average particle diameter was 33 nm, the outer surface acid amount was 0.003 mmol / g, and the acid amount was 0.19 mmol / g.

[0080] The calcium-containing zeolite molded body was used as a catalyst for producing hydrocarbon compounds, and the reaction was carried out for 48 hours as described above. The average yields of each product during the reaction are shown in Table 1. The average yield of light hydrocarbon compounds (the total of ethane, ethylene, propane, and propylene) was 36.6% by weight, the average yield of aromatic compounds (the total of benzene, toluene, and xylene) was 38.3% by weight, and the total yield of light hydrocarbon compounds and aromatic compounds was 74.9% by weight.

[0081] The total yield of light hydrocarbon compounds and aromatic compounds was low, and the productivity was poor.

[0082] Comparative Example 3 The MFI zeolite molded body obtained in Preparation Example 1 was used as a catalyst for producing hydrocarbon compounds, and a reaction was carried out for 48 hours as described above. The average yields of each product during the reaction are shown in Table 1. The average yield of light hydrocarbon compounds (the total of ethane, ethylene, propane, and propylene) was 28.3% by weight, the average yield of aromatic compounds (the total of benzene, toluene, and xylene) was 46.5% by weight, and the total yield of light hydrocarbon compounds and aromatic compounds was 74.8% by weight.

[0083] Priority was given to the production of aromatic compounds, and the production balance and productivity between light hydrocarbon compounds and aromatic compounds was poor.

[0084] [Table 1] [Industrial Applicability]

[0085] The novel silver-alkaline earth metal-containing MFI type zeolite of the present invention makes it possible to realize a stable production method that is excellent in productivity and balance for each of the light hydrocarbon compounds and aromatic compounds, for example, when simultaneously producing them from aliphatic hydrocarbons, and is therefore extremely useful industrially as a catalyst for the simultaneous production of light hydrocarbon compounds and aromatic compounds.

Claims

1. A silver-alkaline earth metal-containing MFI zeolite characterized by satisfying the following characteristics (i) to (v): (i) The average particle diameter (PD) is PD≦100 nm. (ii) The mesopore distribution curve has a peak, the half width (hw) of the peak is hw≦20 nm, the center value (μ) of the peak is 10 nm≦μ≦20 nm, and the mesopore volume (pv) of the mesopores corresponding to the peak is 0.05 ml / g≦pv. (iii) In powder X-ray diffraction measurement at a diffraction angle of 2θ, there is no peak in the range of 0.1 to 3 degrees. (iv) the silver content is 0.05 to 3 wt %; (v) The alkaline earth metal content is 0.05 to 5 wt. %.

2. The silver-alkaline earth metal-containing MFI zeolite according to claim 1, further satisfying any one of the following characteristics (vi) to (viii): (vi) The amount of outer surface acid is 0.01 mmol / g or less. (vii) the acid amount is 0.05 to 0.85 mmol / g; (viii) The weight ratio of silver / alkaline earth metal is 100 / 100 to 500 / 100.

3. 3. The silver-alkaline earth metal-containing MFI zeolite according to claim 1, wherein the alkaline earth metal is at least one selected from the group consisting of calcium, barium and strontium.

4. 4. A catalyst for the simultaneous production of light hydrocarbon compounds and aromatic compounds, comprising the silver-alkaline earth metal-containing MFI zeolite according to claim 1.

5. A method for producing hydrocarbon compounds, comprising contacting an aliphatic hydrocarbon having 4 to 6 carbon atoms at 400 to 800° C. in the presence of the catalyst for simultaneously producing light hydrocarbon compounds and aromatic compounds according to claim 4 to produce C2 to C3 light hydrocarbon compounds and aromatic compounds.

6. The method for producing a hydrocarbon compound according to claim 5, characterized in that the weight ratio of the C2-C3 light hydrocarbon compound / aromatic compound is 80 / 100 to 180 / 100.

Citation Information

Patent Citations

  • Pulse signal control circuit

    JP1979047468A

  • Fish bait

    JP1980064769A

  • Catalyst for producing aromatic hydrocarbon

    JP1998033987A

  • Method for producing ethylene and propylene

    JP2007106739A

  • MFI type zeolite having uniform mesopore and method for producing the same

    JP2013227203A